Pengaruh Brand Image dan Brand Trust terhadap Kepuasan dan Loyalitas Konsumen: Studi pada Konsumen Coffee Mix Kapal Api di Kota Semarang - Abie Husnurridlo; Bambang Sutejo (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study was conducted to identify the influence of brand image, brand trust, and perceived customer satisfaction on customer loyalty. The population in this study was Kapal Api coffee mix consumers in Semarang City. The quantitative analysis method used included a non-probability sampling technique with 86 respondents. The coefficient of determination (R2) was 0.797, meaning that 79.7% of the variation in customer satisfaction can be explained within the analysis period through the identified factors, namely brand image and brand trust. The remaining 25.2% was explained by other factors. Meanwhile, the influence of customer satisfaction on customer loyalty had a coefficient of determination of 0.819, meaning that 81.7% of customer loyalty was simultaneously influenced by customer satisfaction. The results of this study indicate a positive and significant relationship between brand image and brand trust on customer satisfaction, and customer satisfaction has a positive and significant effect on customer loyalty.